Circumstance and Choice : The Role of Initial Conditions and Policies in Transition Economies - de Melo, Martha; Denizer, Cevdet; Gelb, Alan; Tenev, Stoyan (Washington, DC: World Bank, 2014)
This article takes an integrated approach to evaluating the interaction of initial conditions, political change, reforms and economic performance in a unified framework covering 28 transition economies in East Asia, Central and Eastern Europe, and the Former Soviet Union (FSU). Initial conditions and economic policy jointly determine the large differences in economic performance among transition economies. Initial conditions dominate in explaining inflation, but economic liberalization is the most important factor determining differences in growth. Political reform emerges as the most important determinant of the speed and comprehensiveness of economic liberalization, raising the important question of what determines political liberalization. Results suggest the importance of the level of development in determining the decision to expand political freedoms.